The tanshinones from the plant of Salvia miltiorrhiza. (June 2023) - Jiang, Jian-Shuang; Gu, Quan-chang; Feng, Zi-Ming; Yuan, Xiang; Zhang, Xu; Zhang, Pei-Cheng; Yang, Ya-Nan
Abstract: Six undescribed tanshinones, (+) - 2-Cl-tanshindiol C (1 ), (−) - 2-Cl-tanshindiol C (2 ), (+)-tanshinoic acid D (3 ), (−)-tanshinoic acid D (4 ), (−)-tanshinoic acid E (5 ), and (+)-tanshinoic acid E (6 ), were isolated from the rhizome of Salvia miltiorrhiza Bunge. Their structures were elucidated based on the spectroscopic data (UV, IR, HR-ESI-MS, and NMR). The bioactive assays of all these compounds for the antioxidant activities in cardiomyocytes upon hypoxia stimulation were evaluated. The results suggested that compounds 5 and 6 exhibited good antioxidant activities in cardiomyocytes and the cell survival rates were 46.3% and 57.9% (10 −5 mol/L), respectively. Graphical abstract: Image 1 Highlights: Six undescribed tanshinones were isolated from Salvia miltiorrhiza. Compounds 5 and 6 exhibited antioxidant activities in cardiomyocytes. Compounds 1 and 2 contained a rare chlorine heteroatom, while compounds 5 and 6 have a novel spiroketallactone of furanone. Compound structures were elucidated using spectroscopy data. Their absolute configurations were determined by experimental ROESY and ECD spectra.